Associations of dietary polychlorinated biphenyls and long-chain omega-3 fatty acids with stroke risk. (September 2016) - Kippler, Maria; Larsson, Susanna C.; Berglund, Marika; Glynn, Anders; Wolk, Alicja; Åkesson, Agneta
Abstract: Background: Little is known about joint exposure to polychlorinated biphenyls (PCBs) and long-chain omega-3 fatty acids [eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA)], through fish consumption, on cerebrovascular disease risk. Objective: To explore associations of dietary PCB exposure and EPA-DHA intake with risk of different stroke subtypes. Methods: This was assessed in the prospective population-based Cohort of Swedish Men including 39, 948, middle-aged and elderly men, who were free of cardiovascular disease and cancer at baseline in 1997. Validated estimates of dietary PCBs and EPA-DHA were obtained via a food frequency questionnaire. Results: During 12 years of follow-up, 2286 and 474 incident cases of ischemic stroke and hemorrhagic stroke, respectively, were ascertained through register linkage. Dietary PCB exposure and EPA-DHA intake were associated with hemorrhagic stroke but not ischemic stroke. Men in the highest quartile of dietary PCB exposure (median 412 ng/day) had a multivariable- and EPA-DHA-adjusted RR of hemorrhagic stroke of 2.77 [95% confidence interval (CI), 1.48–5.19] compared with men in the lowest quartile (median 128 ng/day; p for trend < 0.01). The corresponding RRs in men with and without hypertension were 5.45 (95% CI, 1.34–22.1) and 2.37 (95% CI 1.17–4.79), respectively. The multivariable- and PCB-adjusted RR of hemorrhagic stroke for the highest quartile of EPA-DHA intake (median 0.73 g/day) versus the lowest quartile (median 0.18 g/day) was 0.42 (95% CI, 0.22–0.79). Conclusion: Dietary PCB exposure was associated with an increased risk of hemorrhagic stroke, whereas a protective association was observed for dietary EPA-DHA intake. Highlights: We explored the link of dietary PCB and EPA-DHA intake with stroke risk in men. Neither dietary PCB nor EPA-DHA was associated with ischemic stroke risk. After mutual adjustment, PCB was associated with increased hemorrhagic stroke risk. Simultaneously, EPA-DHA intake was associated with decreased risk. PCB-associated risk of hemorrhagic stroke was higher among hypertensive subjects.